A Closed-Form Approximation of the Gaussian Noise Model in the Presence of Inter-Channel Stimulated Raman Scattering - Semrau, Daniel; Killey, Robert I.; Bayvel, Polina (Journal of lightwave technology, 2019)
An accurate, closed-form expression evaluating the nonlinear interference (NLI) power in coherent optical transmission systems in the presence of inter-channel stimulated Raman scattering (ISRS) is derived. The analytical result enables a rapid estimate of the signal-to-noise ratio and avoids the need for integral evaluations and split-step simulations. The formula also provides a new insight into the underlying parameter dependence of ISRS on the NLI. Additionally, it accounts for the dispersion slope and arbitrary launch power distributions including variably loaded fiber spans. The latter enables real-time modeling of optical mesh networks. The results is applicable for lumped amplified, dispersion unmanaged, and ultra-wideband transmission systems. The accuracy of the closed-form expression is compared to numerical integration of the ISRS Gaussian noise model and split-step simulations in a point-to-point transmission, as well as in a mesh optical network scenario.